PERSPEKTIF PEMBIAYAAN DALAM MENINGKATKAN KINERJA SEKOLAH (Studi Kasus di SMA IT Cordova 3 Kab. Tangerang) - Qomarudin Khaqiqi, Irfan; Wasliman, Iim; Supyan Sauri, R. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the financial perspective in enhancing schoolperformance through a case study at Arroyyan Cordoba Foundation. This qualitativedescriptive research utilized interviews, observations, and document studies fordata collection. The findings reveal that financial planning at the foundation issystematically carried out through the preparation of the Foundation Budget (ABY),reflecting actual needs and expenditure priorities. Financial implementationprioritizes efficiency and effectiveness with a transparent bookkeeping system.Monitoring and evaluation are conducted periodically to ensure alignment betweenbudget utilization and the foundation's strategic goals. The implementation of thesefinancial strategies positively impacts the foundation's performance, particularly inimproving educational quality through the allocation of funds for students, teachers,and infrastructure. This study recommends strengthening the supervision andaccountability system to support the sustainability of educational funding programs.Keywords: Educational financing, financial management, educational quality,Arroyyan Cordoba Foundation.